The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/s1473-3099(16)30161-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of RTS,S/AS01 malaria vaccine in infants and children with WHO stage 1 or 2 HIV disease: a randomised, double-blind, controlled trial

Abstract: GlaxoSmithKline Biologicals SA and PATH Malaria Vaccine Initiative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 21 publications
1
37
0
Order By: Relevance
“…This renewed confidence in future RTS,S/AS01 vaccine studies and programs involving children with HIV to be pursued. 13 While the RTS,S/AS01 vaccine was shown to confer limited efficacy in both children and infants and limited duration of immunity, 14 it is nevertheless expected to have a significant impact on the high disease burden of this deadly parasitic disease. 15 A malaria vaccine mathematical model showing the supply-and-demand forecast and the impact on public health and financial costs projected that 150 million uncomplicated malaria cases and 1.1 million mortalities would be averted through vaccination over a period of 10 years.…”
Section: Results Of the Pivotal Trialsmentioning
confidence: 99%
“…This renewed confidence in future RTS,S/AS01 vaccine studies and programs involving children with HIV to be pursued. 13 While the RTS,S/AS01 vaccine was shown to confer limited efficacy in both children and infants and limited duration of immunity, 14 it is nevertheless expected to have a significant impact on the high disease burden of this deadly parasitic disease. 15 A malaria vaccine mathematical model showing the supply-and-demand forecast and the impact on public health and financial costs projected that 150 million uncomplicated malaria cases and 1.1 million mortalities would be averted through vaccination over a period of 10 years.…”
Section: Results Of the Pivotal Trialsmentioning
confidence: 99%
“…These include more powerful influenza vaccines, a vaccine against human papilloma virus, a vaccine against malaria, a vaccine against herpes zoster that has shown remarkable efficacy in elderly people, and an improved vaccine against hepatitis B. Probably, the most notable example is the adjuvant AS01, recently licensed for a vaccine against malaria and for a novel herpes zoster vaccine (21,22). This adjuvant is composed of two immunostimulants, the saponin QS21 and monophosphoryl lipid A, targeting TLR4; both compounds are formulated in liposomes.…”
Section: Glycoconjugation a Second Technological Revolution Of The 1mentioning
confidence: 99%
“…Phase IIa/IIb clinical trials of the RTS,S vaccine conducted in Africa showed that it conferred partial protection in adults, children and infants . The phase III clinical trials in seven African countries confirmed that 51% and 33% protection against clinical malaria was achieved 12 months after vaccination in children and infants, respectively . Although the mechanism of the RTS,S/AS01‐induced protective immune response has not been clarified in detail, the anti‐CSP antibodies and CD4 + T‐cell responses induced by vaccination have been correlated with the protection .…”
Section: Introductionmentioning
confidence: 99%
“…8 The phase III clinical trials in seven African countries confirmed that 51% and 33% protection against clinical malaria was achieved 12 months after vaccination in children and infants, respectively. 9,10 Although the mechanism of the RTS,S/AS01-induced protective immune response has not been clarified in detail, the anti-CSP antibodies and CD4 + T-cell responses induced by vaccination have been correlated with the protection. 11 It has been reported that the high-titre antibodies induced by RTS,S/AS01 against the NANP repeat were correlated with the clinical protection.…”
mentioning
confidence: 99%